Epstein–Barr virus-related diffuse large B-cell lymphoma in mogamulizumab-treated adult T-cell leukemia with incomplete T-cell reconstitution - Kamachi, Kazuharu; Shindo, Takero; Miyahara, Masaharu; Kitaura, Kazutaka; Akashi, Michiaki; Shin-I, Tadasu; Suzuki, Ryuji; Oshima, Koichi; Kimura, Shinya (International journal of hematology, 2019)
Adult T-cell leukemia (ATL) is an aggressive mature T-cell malignancy with a poor prognosis. The anti-C–C motif chemokine receptor 4 (CCR4) antibody mogamulizumab (moga) reduces ATL cells and induces reconstitution of polyclonal T cells; however, ATL cases often remain resistant and moga sometimes causes fatal immunopathology. Epstein–Barr virus (EBV)-related B-cell lymphoma develops in severely immunocompromised subjects, and is particularly associated with impaired T-cell immunity. Here, we report an ATL patient who had received conventional chemotherapy plus moga, and subsequently developed EBV-related diffuse large B-cell lymphoma (DLBCL) of the central nervous system. Next-generation sequencing-based T-cell receptor repertoire analyses identified residual abnormal clones and revealed that reconstitution of polyclonal T cells was incomplete, even after moga treatment. Furthermore, a skin rash that developed after moga treatment was found to contain ATL clones. This case suggests that the limited therapeutic effects of moga and incomplete T-cell reconstitution are associated with severely impaired T-cell immunity and subsequent development of EBV-related DLBCL.